Solve the equation 5(x − 3) = 2(x + 6)
Open the brackets ⇒ 5x − 15 = 2x + 12
Subtract 2x from both sides ⇒ 5x – 2x − 15 = 2x − 2x + 12
Tidy up ⇒ 3x − 15 = 12
Add 15 to both sides ⇒ 3x − 15 + 15 = 12 + 15
Tidy up ⇒ 3x = 27
Divide both sides by 3 ⇒ 3x/3 =27/3
⇒ x = 9
total answers (1)
start bookmarking useful questions and collections and save it into your own study-lists, login now to start creating your own collections.
Open the brackets ⇒ 5x − 15 = 2x + 12
Subtract 2x from both sides ⇒ 5x – 2x − 15 = 2x − 2x + 12
Tidy up ⇒ 3x − 15 = 12
Add 15 to both sides ⇒ 3x − 15 + 15 = 12 + 15
Tidy up ⇒ 3x = 27
Divide both sides by 3 ⇒ 3x/3 =27/3
⇒ x = 9
need an explanation for this answer? contact us directly to get an explanation for this answer